2020
DOI: 10.1002/col.22537
|View full text |Cite
|
Sign up to set email alerts
|

Affective matches of fabric and lighting chromaticity

Abstract: This study investigates the impact of lighting colors on subjective judgments of fabric: in particular, whether the influence of lighting varies depending on fabric types and color combinations. We conducted two visual assessments. In Study 1 (N = 44), eight illuminants and six types of fabric were presented as cloth stimuli. Derived from the literature review, four sets of adjectives (humble-luxurious, cool-warm, old-new, and not preferred-preferred) were used as metrics. In Study 2 (N = 41), five sets of fab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…5 There are color attributes such as brightness, chromaticity, and dynamic range that affect how very similar or nearly identical colors appear and can be perceived differently. 6 It has also been found that offices with a chromatic scheme are more pleasing, attractive, satisfying, and dynamic than those with an achromatic scheme. In this respect, the achromatic scheme was found to be more formal and harmonious.…”
Section: Color Preference Through Historymentioning
confidence: 99%
“…5 There are color attributes such as brightness, chromaticity, and dynamic range that affect how very similar or nearly identical colors appear and can be perceived differently. 6 It has also been found that offices with a chromatic scheme are more pleasing, attractive, satisfying, and dynamic than those with an achromatic scheme. In this respect, the achromatic scheme was found to be more formal and harmonious.…”
Section: Color Preference Through Historymentioning
confidence: 99%
“…The A light source can well distinguish the object from the environment and highlight the essential features of the object; note that the coloring result is satisfactory, the picture is saturated with color, and the chroma value is high. The D65 light source is close to daylight and has a cool visual perception, which best objectively reflects the item's color (Kim & Suk, 2020). However, the coloring results of the D65 light source pictures are generally not vivid enough.…”
Section: The Effect Of Illuminants On the Machine Color Emotionmentioning
confidence: 99%
“…There are many types of color combinations, such as adjacent colors, complementary colors, 6,7 tricolors, 8,9 and so on. At present, the related research on color combination selection and design is mainly concentrated in marketing fields such as product design, 10,11 advertising design, 12,13 interior decoration, 14,15 outdoor architecture, 16,17 psychology, 18,19 and computer graphics. 20,21 In other words, the current color combination research mainly focuses on real scenes.…”
Section: Literature Review 21 | Color Combinationmentioning
confidence: 99%